The Validity of Item Tests of Scientific Method of Divergent Patterns in Biology Subject at Senior High Schools Viewed From The Number of Traits - Nur Cahyani, Fajar; Subali, Bambang (Journal of physics. Conference series, 2019)
The initial stage of the research was developing a blue print based on learning continuum, formulating divergent test item models, assigning two experts on measurement and one expert on biological education assessment for reviewing, and performing a try out in the field. The population in this research is the hypothetical population that have characteristics such as selected samples by selecting five Public Senior High Schools in Bantul Regency ranging from schools which have gained highest national examination score to that of the lowest which consist of 954 testee. The data were analyzed using the Quest program referring to the Partial Credit Model (PCM). The analysis was performed to determine the validity of test items which have been developed viewed from single, double, and triple trait. The results of the try out show that all items are fitted with PCM for single and double trait based on INFITMNSQ acceptance limits. Meanwhile, one item is not fitted with PCM for triple trait precisely the trait to investigate. When INFIT-t acceptance limit is employed, some items are not fitted. They include 10 items of single trait, 3 items of double trait precisely the trait to design and perform an investigation and 2 items of the trait to report the results of the investigation. In addition, the non-fitted items for triple trait consist of 3 items of the trait to design an investigation, 2 items of the trait to perform an investigation, and 2 items of the trait to report the results of the investigation.